Cell imaging by phonon microscopy: sub-optical wavelength ultrasound for non-invasive imaging - Perez-Cota, Fernando; Smith, Richard J.; Moradi, Emilia; Leija, Anaid Lugo; Velickovic, Ksenija; Marques, Leonel; Webb, Kevin F.; Symonds, Michael E.; Sottile, Virginie; Elsheikha, Hanny; Clark, Matt (Wiley, 2017)
The mechanical properties of cells play an important role in cell function and behavior. This paper presents recent developments that have enabled the use of laser-generated phonons (ultrasound) with sub-optical wavelengths to look inside living cells. The phonons reveal contrast from changes in the elasticity of the cell and can provide high resolution three dimensional images.